IMPLEMENTING SELF-REFLECTION WRITING IN EFL WRITING CLASS: A CLASSROOM ACTION RESEARCH IN MADRASAH ALIYAH - Marlaini Marlaini (UIN Sumatera Utara, 2021)
Writing is known as the most difficult skill for second language and foreign language learners. One of the strategies much used by teachers, instructors, and practitioners to help the students to overcome the issue is self-reflection writing. This study aimed to find out how the implementation of self-reflection writing could improve students' ability in writing recount text. This research was conducted in a Madrasah Aliyah Swasta Medan. The researchers used classroom action research as the research design, which was conducted in two cycles. In each cycle, the researchers collected both qualitative and quantitative data. Qualitative data were collected through observation sheets, interviews, diary notes and documentation, while quantitative data were obtained from pre-test, post-test I and post-test II. The results of qualitative data showed that: 1) the students felt enthusiastic at the implementation of self-reflection writing; 2) the students became more active in learning to write recount text by using self-reflection writing strategy. Moreover, the results of quantitative data showed that the students reached the minimum score criteria (KKM) in the first cycle with the percentage of 41.1%. In the second cycle, the students gained higher scores with the percentage of 88.2%. Based on the results, it can be concluded that the implementation of self-reflection writing can improve the students’ ability to write recount text.